Overview of searches for dark matter at the LHC. (October 2015) - Mitsou, Vasiliki A
Abstract: Dark matter remains one of the most puzzling mysteries in Fundamental Physics of our times. Experiments at high-energy physics colliders are expected to shed light to its nature and determine its properties. This review talk focuses on recent searches for dark-matter signatures at the Large Hadron Collider, either within specific theoretical scenarios, such as supersymmetry, or in a model-independent scheme looking for mono- X events arising in WIMP-pair production.